Functionaland Nutritional Characterization of Cupcakes Produced from Blends of Mushroom, Orange-Fleshed Sweet Potato and Wheat Flour - Babarinde, Grace O.; Adeola, Lydia T. (Polish Journal of Natural Sciences, 2023)
The increased awareness of healthy eating has necessitated the need for producing healthy and functional foods. This study aimed at producing a healthy nutritious snack containing essential nutrients that are lacking in most conventional cupcakes. This research investigated the quality of cupcakes produced from wheat, orange-fleshed sweet potato (OFSP) and mushroom flour in the ratio 90:5:5; 80:10:10, and 70:15:15, respectively. The control sample was a cupcake produced from 100% wheat flour. The proximate composition, total phenolic, vitamin A content, and sensory properties of the cupcakes, as well as some functional properties of the flour blend, were determined. The protein, ash and crude fibre of cupcakes increased as levels of mushroom and OFSP flours in the cupcake increased. Phenolic content of the cupcakes ranged from 0.13 to 0.16 mg/g and vitamin A content ranged from 0.64 to 1.06 mg/100 g. Functional properties of the flour sample ranged from 72.00-94.67%, 6.97-8.19% and 0.70-0.67 g/ml for water absorption capacity, swelling capacity and bulk density, respectively. The developed cupcakes had improved nutritional composition.